Mechanical Properties of Graphene-Modified Epoxy Grout for Pipeline Composite Repair - Nurfarahin, Zainal; Hanis Hazirah, Arifin; Zardasti, Libriati; Nordin, Yahaya; Lim, Kar Sing; Norhazilan, Md Noor (Penerbit UTHM, 2018)
In general, when the pipeline experiences metal loss on the external surface, epoxy grout has always be used to fill the gap before fibre reinforced composite can be applied to recover the pipeline strength. In this research, the existing commercially available epoxy grout has been strengthened using graphene nanoplatelets (GNPs) at the amount of 0.1wt% to enhance its mechanical properties. Various mechanical tests were conducted on this modified epoxy grout to identify the compression, tensile, flexural and shear properties and were compared to the neat epoxy grout to observe its potential improvement. GNPs were dispersed using a sonication process followed by three-roll milling technique to ensure a uniform and homogeneous dispersion within the epoxy matrix can be well achieved. The experimental results clearly show an improvement in the strength and Young’s modulus especially for tensile, flexural and lap shear test by incorporating GNPs as additives. The presence of GNPs has a significant reinforcement effect and has succeeded in increasing the ductility of the grout, thus reducing its brittle behaviour. This gives an indication that the performance of modified epoxy grout is expected to be reliable and capable to minimize sudden rupture of the pipeline due to bursting.